2013
DOI: 10.1016/j.robot.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Piecewise linear spine for speed–energy efficiency trade-off in quadruped robots

Abstract: h i g h l i g h t s• Effects of flexible spine on performance of bounding quadrupeds are studied.• Superiority of nonlinear spines over linear ones is shown.• High performance is explained by energy storage-release profile of nonlinear springs.• Results are justified through a behavioral analogy with biology. a r t i c l e i n f o t r a c tWe compare the effects of linear and piecewise linear compliant spines on locomotion performance of quadruped robots in terms of energy efficiency and locomotion speed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Realization limitation may impose other constraints like monotony on compliance profile ( [12]). In [1], we show that nonlinearity in compliance profile gives us a flexibility in energy store-release shape of compliance, and subsequently improves energy efficiency of the system. In this work, our design methodology, based on the natural dynamics, results in a nonlinear parallel compliance.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Realization limitation may impose other constraints like monotony on compliance profile ( [12]). In [1], we show that nonlinearity in compliance profile gives us a flexibility in energy store-release shape of compliance, and subsequently improves energy efficiency of the system. In this work, our design methodology, based on the natural dynamics, results in a nonlinear parallel compliance.…”
Section: Introductionmentioning
confidence: 87%
“…Here are some instances: in a linear system, spring constant can relocate poles of the system and subsequently affect stability. Shaping the compliance to store energy and release it in a desired manner can lead to energy efficiency [1]. In SLIP model, average forward velocity can be controlled by leg compliance [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that a spinal joint with a spring can improve the overall energy-efficiency of the robot [45]. Others have shown that a spine with nonlinear stiffness leads to even higher efficiency [77]. In our robot, the front and rear body will be made to bounce on their legs, while the flexible spine introduces a resonance that results in forward motion.…”
Section: Hoppersmentioning
confidence: 98%
“…Taking their inspiration from nature, many other scientists have investigated robotic quadrupeds with a spine: studying linear or rotational spinal joints, actuated and unactuated versions, or passive slope-walkers [77,111,33,76]. It is clear that a spine can contribute positively to locomotion.…”
Section: Synchronised Circling Masses §5 Conclusionmentioning
confidence: 99%